Property rights and misallocation: Evidence from land certification in China - Gao, Xuwen; Shi, Xinjie; Fang, Shile (World development, 2021)
•Land certification leads to land and labor reallocation to more efficient farms with positive aggregate effects.•The reform increases renting-out by low-productivity farmers and renting-in by more productive farmers.•Low-productivity households are more likely to have migrants than high-productivity households. Employing 2015 and 2017 CFD data, this paper studies how the new round of a land certification program that aims to provide secure land titles for farmers has affected factor reallocation and aggregate output in China. The main findings are that land certification results in well-defined and secure property rights and leads to land and labor reallocation to more efficient farms with positive aggregate effects. Our paper also provides direct evidence of the reallocation mechanism by showing that the reform increases renting-out by low-productivity farmers and renting-in by more productive farmers. Moreover, the reform changes the likelihood of households remaining in agriculture: low-productivity households are more likely to have migrants than high-productivity households.